2019
DOI: 10.1111/tbed.13044
|View full text |Cite
|
Sign up to set email alerts
|

Detection of reassortant avian influenza A (H11N9) virus in wild birds in China

Abstract: Human infectious avian influenza virus (AIV) H7N9 emerged in China in 2013. The N9 gene of H7N9, which has the ability to cause death in humans, originated from an H11N9 influenza strain circulating in wild birds. To investigate the frequency and distribution of the N9 gene of the H11N9 and H7N9 influenza virus circulating in wild birds between 2006 and 2015, 35,604 samples were collected and tested. No H7N9 but four strains of the H11N9 subtype AIV were isolated, and phylogenetic analyses showed that the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…This observation suggested that cocirculation of these viruses may predispose toward reassortment events to produce further genotypes with unknown disease risks to both poultry and humans. The continued circulation of H7N9 and H9N2 viruses with other AIV subtypes, enzootic in farmed and wild bird populations, has resulted in emergence of novel reassortant viruses with variable pathogenesis, along with the potential for mammalian adaptation and zoonotic transmission ( 17 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggested that cocirculation of these viruses may predispose toward reassortment events to produce further genotypes with unknown disease risks to both poultry and humans. The continued circulation of H7N9 and H9N2 viruses with other AIV subtypes, enzootic in farmed and wild bird populations, has resulted in emergence of novel reassortant viruses with variable pathogenesis, along with the potential for mammalian adaptation and zoonotic transmission ( 17 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the H11 HA and N9 NA genes showed high sequence similarity to the corresponding genes of isolates from wild birds in South Africa and Spain, respectively, and did not cluster in the major groups with recent wild-bird isolates from East Asia, suggesting that dynamic movements of wild birds in Japan occur in the Izumi plain. Previously, H11N9 in China was detected from avian birds in 2006-2015 and in environmental samples from live poultry markets in China in 2016 [69]. This indicates that Chinese H11N9 obtained the potential for transmission from avians to poultry.…”
Section: Discussionmentioning
confidence: 96%
“…H11N9 has been found in wild birds in Brazil, Europe, and Japan [14,17,19,21,22,69,70]. Japan is an overwintering site of endangered cranes (hooded cranes and white-naped cranes) and many other migratory birds (including wild ducks), which are considered as carriers of AIVs [70].…”
Section: Discussionmentioning
confidence: 99%
“…First, poultry infected with H9N2 AIV will display clinical symptoms such as egg reduction. Typically, a substantial amount of poultry is kept in large and intensive environments on farms, and due to the high transmissibility of low-pathogenicity avian influenza virus, the economic impact of an outbreak of AIV can be incredibly damaging [3][4][5]. In addition, chickens infected with AIV are more likely to be coinfected with other pathogens due to the low resistance of the immune system, resulting in a high fatality rate [6,7].…”
Section: Introductionmentioning
confidence: 99%